MentAlzh: Mobile Application Prototype for Early Detection of Cognitive Impairment - Hurtado, Andrés F.; Marín, Kelly D.; Paredes, Carlos M.; Gómez, Daniel; Rey Piedrahita, Andrés (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The increasing incidence of neurodegenerative diseases has raised a pressing need for practical tools to detect mild cognitive impairment in its early stages. This study presents MentAlzh, a mobile app prototype that employs an interactive multimedia approach to cognitive assessment, adapting traditional methods. The app was developed using the design thinking methodology to engage the end-user; the prototype encompasses six cognitive tests inspired by established methods, focusing on orientation, clock drawing, fixation, language, calculation, and memory. A group of 21 participants, aged between 51 and 76, evaluated the app regarding usability, accuracy, and repeatability. Results demonstrated consistent performance on orientation and fixation tasks, while variability on memory and clock drawing tests indicated potential areas for further refinement. The MentAlzh prototype was found to have the potential to serve as an accessible and user-friendly tool for early cognitive screening.